Kinetic and isothermal study of dye absorption using pre-treated natural fabrics using polyamine compounds - Eman M. Reda; Hanan A. Othman; Heba Ghazal; Ahmed G. Hassabo (Scientific Reports)
Abstract The study examined the use of cationic polymers (Polyethyleneimine and chitosan) in treating fabrics like cotton, wool, and cotton/wool (70/30) to improve their dyeability and printability. The study examined factors such as dye concentration, time, and temperature for the dyeing process. Results showed that all dyed and printed fabrics treated with polyethyleneimine and chitosan increased color strength by significant percentages. Fastness properties, such as washing, rubbing, acidic and alkaline perspiration, and lightness, improved significantly. Fabric roughness, tensile strength, and elongation decreased by about 4-10% for each fabric. Additionally, the dyed and printed fabrics showed high resistance to bacteria and fungi. The study contributed to reducing chemicals used in traditional dyeing processes by a significant percentage, as the dyeing bath contained only the treated sample and dye solution. Furthermore kintic and isothermal study was investigated to explain the behaviour of treated fabrics for dye absorption.